Tropomyosin-related kinase A (TrkA) inhibition for the treatment of painful knee osteoarthritis: results from a randomized controlled phase 2a trial. Issue 11 (November 2019) - Watt, F.E.; Blauwet, M.B.; Fakhoury, A.; Jacobs, H.; Smulders, R.; Lane, N.E.
Summary: Objective: To investigate the TrkA inhibitor, ASP7962, for treatment of painful knee osteoarthritis. Design: Phase 2a, double-blind, placebo- and naproxen-controlled, double-dummy, parallel-group study. Adults with knee osteoarthritis were randomized (2:2:1) to ASP7962 (100 mg), placebo, or naproxen (500 mg) twice daily (BID) for 4 weeks. Primary endpoint: change from baseline to Week 4 in Western Ontario and McMaster Universities Arthritis Index (WOMAC) pain subscale score. Secondary endpoints: change from baseline to Weeks 1, 2, and End of Treatment (EoT) in WOMAC pain subscale score; change from baseline to Weeks 1, 2, 4, and EoT in WOMAC physical function and stiffness subscales, walking pain and WOMAC total scores; and change from baseline in daily average pain score. Results: 215 participants were randomized (ASP7962 100 mg BID, n = 85; placebo, n = 87; naproxen 500 mg BID, n = 43). No significant difference was observed between ASP7962 and placebo in change from baseline to Week 4 in WOMAC pain subscale score (−0.14; 90% 2-sided CI: −0.62, 0.34; P = 0.316); a significant difference was observed between naproxen and placebo (−0.67; 80% 2-sided CI: −1.12, −0.23; P = 0.027). No differences were observed between ASP7962 and placebo in change from baseline in any WOMAC subscale score; statistically significant changes were observed between naproxen and placebo ( P ≤ 0.01, all time points for all WOMAC endpoints). ASP7962 was safe and well-tolerated. Conclusions: Four-week treatment with ASP7962 (100 mg BID) did not improve pain or physical function in individuals with painful knee osteoarthritis. ClinicalTrials.gov, NCT02611466 ; EudraCT Number, 2014-004996-22.